Wildfires, forest management and landowners⿿ collective action: A comparative approach at the local level. (November 2016) - Canadas, Maria João; Novais, Ana; Marques, Marco
Highlights: ⿢ Collective action for wildfire risk reduction has different territorial constraints. ⿢ Ideal landscape management units can originate large and inefficient group sizes. ⿢ Risk reduction is more needed where collective action⿿s transaction costs are higher. ⿢ Market incentives for fuel treatments are lower in the most fire-prone landscapes. ⿢ Public policy can exacerbate territorial disadvantages for collective risk reduction. Abstract: The increase in frequency and extent of fires in Portugal has favoured the approval of a new legal frame for forest management, the Forest Intervention Zone (FIZ). Under this frame, a large contiguous surface involving numerous owners is subject to a single management plan, providing an opportunity for cooperation. Since 2005, 161 zones have been created but only half of them have had their management plan approved and very few are nearing its implementation. Cooperation amongst private forest owners has usually been explained at the owner level. In an approach at the local level we examine local constraints and key-factors for cooperative landscape management. Building on the theory of collective action, a typology of FIZ/territories is established by Cluster Analysis using a group of ecological and socioeconomic variables expressing the characteristics of natural resources, owners⿿ group, institutional arrangements, and external environment of FIZs. Three clusters are identified. Where FIZs are smaller and biophysical resources impose greater wildfire susceptibility, the transaction costs for collective management are highest due to more numerous, aged, and dispersed owners and the absence of a land registry. Conversely, larger FIZs have fewer owners, more powerful management bodies, and higher public financial incentives, leading to greater performance rate. Nonetheless, since their resources are less fire-prone, and private profitability is higher, public support for collective action has a lower social return. Addressing the heterogeneity of local systems of ecological and socioeconomic constraints is therefore a challenge faced by public policy makers seeking to mitigate wildfire risk.